Design and Build Inventory System using EOQ and ROP Methods (Case Study: CV. Ziefa Karya) - Lubis, Rapida Hanim; Nasution, Fitri Aini; Juledi, Angga Putra (Politeknik Ganesha Medan, 2022)
As a construction company that manages large quantities of incoming and outgoing goods, CV. Ziefa Karya must carry out an inventory control process, to determine the number of products to be re-supplied in a fast and accurate manner. But what happened was the opposite, with the inventory control process that was still manual, the owner of the company experienced various losses because he did not record goods and went out regularly. Based on these problems, this study tries to provide a solution in order to facilitate the management of inventory. CV. Ziefa Karya must have an inventory system that can manage the supply of goods properly. This study aims to build an inventory system based on information systems on CV. Ziefa Karya by applying the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods. The system development method used is Model Driven Development (MDD) which includes: interviews, observations, literature studies, problem analysis, needs analysis, design, construction, and implementation. From the results of implementation and testing, it is found that the implementation of EOP and ROP in the application has succeeded in making the inventory system function properly. From these results it can be concluded that to build an inventory system on CV. Ziefa Karya uses the EOQ and ROP methods which can provide fast, precise, and accurate information, so the Model Driven Development (MDD) method must be used.